PELAKSANAAN PEMBELAJARAN KEYBOARD DASAR DI SMP NEGERI 9 PADANG - Indah Komala Sari; Syahrel Syahrel; Yos Sudarman (SENDRATASIK UNP, 2013)
Abstract   This research aims at describing the implementation of Basic Keyboard musical instrument at SMP Negeri 9 Padang. This qualitative research used descriptive methods. Main instrument of the research was the researcher herself supported by tools to collect the data, such as, observation note, and documentation. Therefore, technique of collecting data refered to field observation technique. The result of the research showed that the learning of keyboard at the junior high school could not enter to technique of playing as a whole. As it should be started by introducing every part of the keyboard, how to use them, fingers technique, chord knowledge, figures notations and then supporting by the explanation about musical material. It was done as the students has lack of knowledge about the implementation of learning keyboard at SMP Negeri 9 Padang.